Kesalahan Berbahasa Bidang Fonologi pada Akun Youtube Nihongo Mantappu: “Wasedaboys jadi Guru Jepang di SMA Indonesia! Gimana Ya!?” - Setiawan, Aldi; Damastina, Biona (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The aim of this research is to explain language errors at the phonological level in the Nihongo makanpu YouTube account videos by using the example of the video entitled "Wasedaboys Become Japanese Teachers in Indonesian High Schools! How's That!?". This research applies a qualitative approach with descriptive methods used in this research and the research subject is the video. The data collection method used was the proficient free-involved listening technique (SBLC). The results of the research show that there are language errors at the phonological level in the video, with 11 data found, consisting of 2 phoneme change data, 5 phoneme deletion data, and 4 phoneme addition data. Therefore, the language errors at the phonological level that occurred in this study are common in people who are just learning to speak a language that is not their mother tongue or beginner foreign speakers.